Incremental Prognostic Value of Guideline-Directed Medical Therapy, Transradial Access, and Door-to-Balloon Time on Outcomes in ST-Segment–Elevation Myocardial Infarction. (March 2019) - Huded, Chetan P.; Kumar, Anirudh; Johnson, Michael; Abdallah, Mouin; Ballout, Jad A.; Kravitz, Kathleen; Menon, Venu; Gullett, Travis C.; Hantz, Scott; Ellis, Stephen G.; Podolsky, Seth R.; Meldon, Stephen W.; et al.
Abstract : Background: Systems to improve ST-segment–elevation myocardial infarction (STEMI) care have traditionally focused on improving door-to-balloon time. However, prompt guideline-directed medical therapy and transradial primary percutaneous coronary intervention (PCI) are also associated with reduced STEMI mortality. The incremental prognostic value of each facet of STEMI care on clinical outcomes within a STEMI system of care is unknown. Methods and Results: We implemented systems-based strategies at our hospital to improve 3 STEMI care metrics: (1) prompt guideline-directed medical therapy before sheath insertion for PCI, (2) use of transradial primary PCI, and (3) door-to-balloon time. We assessed the incremental association of metrics achieved with in-hospital adverse events and 30-day mortality. Of 1272 consecutive patients with STEMI treated with PCI at our hospital (January 1, 2011, to December 31, 2016), the percentage with achievement of zero, 1, 2, or 3 STEMI care metrics was 7.1%, 24.1%, 43.8%, and 25.1%; and 30-day mortality was 15.6%, 8.6%, 3.6%, and 3.2%, respectively (log-rank P <0.001). After adjusting for known clinical predictors of STEMI in-hospital mortality, achievement of at least 2 STEMI care metrics was associated with significantly reduced in-hospital mortality (odds ratio, 0.39; 95% CI, 0.16–0.96; P =0.041). Each metric provided incremental prognostic value when modeled in stepwise order of their occurrence in clinical practice (final model C statistic, 0.677; P <0.001). Conclusions: Prompt guideline-directed medical therapy before sheath insertion for PCI, transradial primary PCI, and door-to-balloon time add incremental prognostic value in STEMI care. Expanding STEMI systems of care from a singular focus on door-to-balloon time to a comprehensive focus on multifaceted STEMI care offers an opportunity to further improve STEMI outcomes.